Muscle Activation During Grasping With and Without Motor Imagery in Healthy Volunteers and Patients After Stroke or With Parkinson's Disease - Kobelt, Manuela; Wirth, Brigitte; Schuster-Amft, Corina (Frontiers in Psychology, 2018)
Introduction: The present study assessed whether motor imagery (MI) produces electromyographic activation in specific muscles of the upper limb during a hand grasping and arm-lifting task in healthy volunteers, patients after stroke, or with Parkinson’s disease. Electromyographic (EMG) activation was compared under three conditions: motor imagery (MI), physical execution (PE), and rest. The task is clinically relevant unilateral executed movement using open muscle chains. Methods: In a cross-sectional study EMG activation was measured in four muscles: M. deltoideus pars clavicularis, M. biceps brachii, M. extensor digitorum, M. flexor carpi radialis. MI ability was evaluated with mental rotation, mental chronometry and the Kinaesthetic and Visual Imagery Questionnaire. Cognitive performance was screened with the Mini-Mental State Examination. Results: Twenty-two participants (11 females, age 52.6±15.8, age range 21 to 72) were included: ten healthy volunteers, seven patients after stroke (time after stroke onset 16.3±24.8 months), and five patients with Parkinson’s disease (disease duration 60.4±24.5 months). Overall Mini-Mental State Examination scores ranged between 27 and 30. An increased EMG activation during MI compared to rest condition was observed in M. deltoideus pars clavicularis and M. biceps brachii across all participants (p-value=0.001, p=0.007). Seven participants (two healthy volunteers, three patients after stroke and two patients with Parkinson’s disease) showed a EMG activation during MI of the hand grasping and arm-lifting task in at least one of the target muscles. No correlation between EMG activation during MI and scores of three MI ability assessments were found. Conclusions: The findings suggest that MI can yield subliminal EMG activation. However, that might vary on individual basis. It remains unclear what parameters contribute to or inhibit an EMG activation during MI. Future investigations should determine factors that influence EMG activation, e.g. MI instructions, tasks to imagine, amount of MI training, and longitudinal changes after an MI training period.